Law as a source of pluralism?. (May 2015) - Preuß, Ulrich K.
This article builds upon the distinction between pluralism and plurality, the latter in the sense of variety or diversity. Plurality is an empirical fact, such as the biological diversity of the human species. In contrast, pluralism is a normatively underpinned social pattern according to which the diversity of interests, opinions, values, ideas, etc., of individuals and groups is recognized as a constitutive element of a political order. Pluralism can materialize only if a political order is not based upon the claim of one undisputable truth. An embryonic form of pluralism through law emerged in ancient Greece with the institution of courts in which the parties to a legal dispute could argue over what the law said and hence officially present divergent meanings of justice. For the modern development the separation of law and justice was a major step towards pluralism insofar as the authority of the polity and the binding force of the law were no longer based upon the contention of one exclusive truth – auctoritas, non veritas facit legem . This Hobbesian principle banned religious, moral, philosophical and political discourses to the pre-political domain of privacy and secrecy from which pluralism could not result. Referring to the distinction between regulative and constitutive norms I submit that only the latter, not the former, can function as sources of pluralism.